Digital Tools and Technical Views: The Intersection of Digital Art History and Technical Art History in a Digital Archive on the Painting Technique of Caravaggio and His Followers. (3rd April 2019) - Cardinali, Marco
Abstract : Digital art history is currently moving into a new phase. As a result of the ongoing digitization of artifacts and the creation of large digital repositories that bring together literary sources, images, as well as historical and technical data, new perspectives point to data mining and data/image processing. This article reviews some of the main data and image bases that deal with technical and material studies on works of art. The work-in-progress, Technical Data/Image Base on Caravaggio and His Followers, of the Max Planck Institut für Kunstgeschichte/Bibliotheca Hertziana (Rome, Italy) is presented within a historical and theoretical framework, describing the establishment of technical research in art history and the role played as early as 1930 by the International Conference for the Study of Scientiﬁc Methods in the Examination and Conservation of Artworks (Rome). The state of the art of technical research on the Italian painter Michelangelo Merisi, Il Caravaggio (1571–1610) and its critical issues are also sketched out, and the nature of the scientific information provided by digital multispectral imaging is considered within a brief review of the history of technical images.